2013
DOI: 10.1530/boneabs.1.pp2
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw in a patient with rheumatoid artritis treated with an oral aminobisphosphonate: a clinical case report

Abstract: SummaryOsteonecrosis of the jaw (ONJ) has been recently described after intravenous administration of amino-bisphosphonates and -less frequently -in association with the use of oral bisphosphonates. Bisphosphonate-Related Osteonecrosis of the Jaw (BRONJ) may affect mandible bone (65%), maxilla bone (26%) and rarely (9%) both sites simultaneously. Although causality may never be proven, emerging experimental data have established a strong association between monthly intravenous bisphosphonate administration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…3) Many patients with RA are treated by bisphosphonates (BP) for management of osteoporosis, and potentially they are prone to jaw necrosis even with oral BP ( 17 ) especially in presence of periodontitis ( 18 ),…”
Section: Introductionmentioning
confidence: 99%
“…3) Many patients with RA are treated by bisphosphonates (BP) for management of osteoporosis, and potentially they are prone to jaw necrosis even with oral BP ( 17 ) especially in presence of periodontitis ( 18 ),…”
Section: Introductionmentioning
confidence: 99%
“…They showed that SR has short-term stimulating effect on bone formation, and is associated with a long-term increase in BMD. Longato et al reported a case of BRONJ in a patient with rheumatoid arthritis 7. The patient was switched from BP to SR after the occurrence of BRONJ, but the effect of SR treatment was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a 10-year clinical trial finds that SR reduces the risk of vertebral and non-vertebral fractures, and increases bone mineral density (BMD) 6. Yet, few reports detail surgical interventions followed by daily SR for osteoporosis patients suffering BRONJ 7. Here, we present the case of a postmenopausal woman with osteoporosis who suffered from ONJ related to long-term oral BP consumption.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cancer patients have been reported to be at a higher risk for ONJ, with a prevalence of 1.5%. In Australia, an average prevalence of 1.15% was reported in cancer patients, reaching 7.8% in those undergoing dental work (11,12). In another study, patients with myeloma had a prevalence nearly double (55.9%) that of patients with BC (33.4%) or prostate cancer (4.6%), despite all three groups being treated for metastatic bone lesions with zoledronate or pamidronate by the same protocol (12).…”
Section: Discussionmentioning
confidence: 99%